2020
DOI: 10.1111/ases.12790
|View full text |Cite
|
Sign up to set email alerts
|

Clinical prospects for laparoscopic stoma closure of a temporary loop ileostomy: Initial experience and report

Abstract: Introduction: In closure of a stoma, the small working space and adhesions hinder a precise surgical procedure, compared with conventional approaches to digestive surgery. The aim of this prospective study was to introduce a new technique of laparoscopic stoma closure (LASC). Materials and surgical techniques: After starting with three trocars, it is a priority to dissect around the arising ileum; a linear stapler is precisely inserted in both orifices of the loop stoma and applied two times, extracorporeally.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 20 publications
0
2
0
Order By: Relevance
“…5 Study done by orlado baba yllan et al showed mean age of 46 years. 6 Study done by Rodrigues oliva perez et al showed mean age of 56 years. 7 Study done by Asadullah Khan et al showed mean age of 41.5 years.…”
Section: Discussionmentioning
confidence: 97%
“…5 Study done by orlado baba yllan et al showed mean age of 46 years. 6 Study done by Rodrigues oliva perez et al showed mean age of 56 years. 7 Study done by Asadullah Khan et al showed mean age of 41.5 years.…”
Section: Discussionmentioning
confidence: 97%
“…With the evolution of minimally invasive techniques, laparoscopic-assisted reversal has been developed to reduce postoperative complications such as bowel obstruction and incisional hernia (5,6). In addition, some initial explorations of laparoscopic reversal with intracorporeal anastomosis have been conducted (7)(8)(9). However, intracorporeal intestine reconstruction is relatively difficult and requires a learning process for inexperienced surgeons.…”
Section: Introductionmentioning
confidence: 99%